1997
DOI: 10.1093/jnci/89.4.293
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Generation of Human Cytotoxic T Lymphocytes Specific for Peptides Derived From Prostate-Specific Antigen

Abstract: Our studies form a rational basis for the use of PSA peptides or recombinant vectors encoding PSA in the development of anticancer vaccine immunotherapy protocols for patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
1
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(138 citation statements)
references
References 31 publications
2
128
1
3
Order By: Relevance
“…Neither the MUC-1-specific nor the PSA-specific T-cell line lysed the melanoma line, which is negative for both PSA and MUC-1. Previous studies (10,38) have shown that the CD8 + T-cell lines generated by both PSA and MUC-1 peptides employed here are MHC restricted.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Neither the MUC-1-specific nor the PSA-specific T-cell line lysed the melanoma line, which is negative for both PSA and MUC-1. Previous studies (10,38) have shown that the CD8 + T-cell lines generated by both PSA and MUC-1 peptides employed here are MHC restricted.…”
Section: Resultsmentioning
confidence: 87%
“…Theses included the generation of T cells directed against PSMA, PAP, PSCA, and/or MUC-1 ( In light of the ELISPOT results in which we observed generation of a T-cell response postvaccination to both PSA and MUC-1, we conducted studies to determine if we can generate T-cell lines from the postvaccination PBMCs that were specific for either PSA or MUC-1 epitopes. The 10-mer PSA and MUC-1 peptides used have been described previously (10,38). Autologous dendritic cells were pulsed with PSA or MUC-1 peptide to generate T cells from PBMC as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the choice of the different monitoring tools is a matter of constant debate (Keilholz et al, 2002;Coulie and van der Bruggen, 2003). Although HLA A2-restricted PSA-derived peptides have been identified (Correale et al, 1997;Chakraborty et al, 2003), the use of peptides for immunological monitoring significantly limits the number of evaluable patients, when whole antigen vaccines are used. This was recently documented by Gulley et al (2002) in a trial with a recombinant vaccinia vector encoding PSA, where only five of the 42 enrolled patients could be immunologically tested.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, two synthetic decamer (10-mer) peptides corresponding to residues 141-150 and 154-163 of PSA were able to elicit CTL responses in vitro from normal HLA-A2 þ volunteers. 139 We have recently used tetramers for three PSA-derived peptides to directly quantify PSA-specific CD8 þ T cells in peripheral blood of non-vaccinated patients with PC and compared with a control group without cancer. 89,140 An example of visualization of PSA-specific CD8 þ T cells using tetramer staining is shown in Figure 3.…”
Section: Prostate-associated Antigens Recognized By Cd8 þ T Lymphocytmentioning
confidence: 99%